Ramadan and the Quran - Khan, Saniyasnain (Goodword Books: New Delhi, 2004)
The book explains that the Quran was first revealed during the month of Ramadan, making this month especially significant for Muslims. It emphasizes the importance of fasting, prayer, and charity during Ramadan, teaching children about the spiritual practices and values associated with this holy month. Through simple text and vibrant illustrations, the book aims to instill an understanding of Ramadan's significance in an engaging and age-appropriate manner.